Методы синтеза информационных компонент с формальными моделями системы функционирования книжно-журнальных изданий - Петриашвили, Г. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
This article is about the problems of synthesis of formal logic models that are
used to describe the processes occurring in the system functioning book and magazine
editions. Based on this it was done the assertion of the consistency of the model
synthesized from formal logic models and information models, that is one of the basic
informational component.